Rapid preparation of adherent mammalian cells for basic scanning electron microscopy (SEM) analysis - Andrew, Osahor; Karthik, Deekonda; Choon, Weng Lee; Ui, Edmund Hang Sim; Aurelian, Radu; Kumaran, Narayanan (Academic Press Inc., 2017)
Sample preparation for scanning electron microscope analysis involves reagents and equipment that are expensive and often hazardous. Here we demonstrate a circumvention of Osmium tetroxide and critical point drying, greatly reducing the duration, complexity and cost of the process. We captured early stage interactions of invasive-bacteria and HeLa cells during the process of bacteria-mediated gene delivery and illustrate sufficient clarity can be obtained using this procedure to preserve and clearly visualize relevant cellular structures. This protocol is significantly cheaper and easier to adapt compared to conventional methods, and will allow routine preparation/viewing of eukaryotic or bacterial samples for basic morphological studies.